PERENCANAAN BIAYA MENGGUNAKAN PERHITUNGAN BIAYA RIIL PADA PROYEK PERUMAHAN - Mohammad Djaelani; Arif Rachman Putra; Didit Darmawan; Utami Puji Lestari; Eli Retnowati (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
In the implementation of construction projects, several stages need to be carried out before the main activities are carried out. Construction activities start from a feasibility survey on site, design, budgeting, construction implementation, and evaluation. In order to be able to carry out all activities, contractors need to implement construction management in order to ensure the work runs with minimal obstacles and achieves success. An important stage in construction activities is cost budgeting. Budgeting is structured based on the principles of effectiveness of results and cost efficiency. Some contractors always skip this stage because they have experience or carry out small construction activities. As a result, construction activities stopped temporarily and could not even continue. This study aims to determine budget management to perform cost calculations on housing development activities. The study was conducted in a construction project in Alana Regency Cerme, Cerme District, Gresik. Based on the calculation of the budgeting, it is obtained costing with an estimated value of Rp. 222,287,554.55. In the implementation of the construction obtained a total cost of Rp. 206,632,729.55. This shows the existence of a profit with a value of Rp. 15,654,825.00.